“They give students too much for their age”: Toward deep learning from primary school teachers’ perspective through interpretive phenomenology - Sani Sahara; Mohammad Idham Chaled; Fizar Indrawijaya; Nadya Syifa Utami; Phoong Seuk Yen (UNION : Jurnal Ilmiah Pendidikan Matematika, 2025)
The Indonesian Deep Learning “Pembelajaran Mendalam” initiative represents an effort to address long-standing deficits in students’ critical thinking and higher-order skills. However, for teachers on the ground, the policy often collides with a very different reality. This interpretive phenomenological study explores the challenges associated with the initiative by focusing on the lived experiences of elementary school teachers in South Jakarta as they navigate the new mandate. Rather than measuring implementation fidelity, the analysis reveals the difference between policy and teachers’ everyday experience. Teachers describe a professional world dominated by the immediate demands of classroom management, in which abstract policy goals feel largely unattainable. They express a deep sense of overload—both logistical and developmental—arguing that the curriculum demands forms of philosophical reasoning from children who are still mastering basic concrete concepts. Moreover, the implementation is experienced visible in workshops and policy documents but failing in daily classroom practice. This study contributes to the literature by demonstrating that the difficulties surrounding Pembelajaran Mendalam not from teacher resistance but from a policy design that insufficiently accounts for the developmental and practical realities of elementary education.